Later emergence of acquired drug resistance and its effect on treatment outcome in patients treated with Standard Short-Course Chemotherapy for tuberculosis. Issue 1 (December 2016) - Gao, Jingtao; Ma, Yan; Du, Jian; Zhu, Guofeng; Tan, Shouyong; Fu, Yanyong; Ma, Liping; Zhang, Lianying; Liu, Feiying; Hu, Daiyu; Zhang, Yanling; Li, Xiangqun; et al.
Abstract Backgrounds The failure of current Standard Short-Course Chemotherapy (SCC) in new and previously treated cases with tuberculosis (TB) was mainly due to drug resistance development. But little is known on the characteristics of acquired drug resistant TB during SCC and its correlation with SCC failure. The objective of the study is to explore the traits of acquired drug resistant TB emergence and evaluate their impacts on treatment outcomes. Methods A prospective observational study was performed on newly admitted smear positive pulmonary TB (PTB) cases without drug resistance pretreatment treated with SCC under China's National TB Control Program (NTP) condition from 2008 to 2010. Enrolled cases were followed up through sputum smear, culture and drug susceptibility testing (DST) at the end of 1, 2, and 5 months after treatment initiation. The effect factors of early or late emergence of acquired drug resistant TB, such as acquired drug resistance patterns, the number of acquired resistant drugs and previous treatment history were investigated by multivariate logistic regression; and the impact of acquired drug resistant TB emergence on treatment failure were further evaluated. Results Among 1671 enrolled new and previously treated cases with SCC, 62 (3.7 %) acquired different patterns of drug resistant TB at early period within 2 months or later around 3–5 months of treatment. Previously treated cases were more likely to develop acquired multi-drug resistant TB (MDR-TB) (OR, 3.8; 95 %CI, 1.4–10.4;P  = 0.015). Additionally, acquired MDR-TB cases were more likely to emerge at later period around 3-5 months after treatment starting than that of non-MDR-TB mainly appeared within 2 months (OR, 8.3; 95 %CI, 1.7–39.9;P  = 0.008). Treatment failure was associated with late acquired drug resistant TB emergence (OR, 25.7; 95 %CI, 4.3–153.4;P  < 0.001) with the reference of early acquired drug resistant TB emergence. Conclusions This study demonstrates that later development of acquired drug resistant TB during SCC is liable to suffer treatment failure and acquired MDR-TB pattern may be one of the possible causes.